Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $f(x)=x^2+2x$ and $g(x)=x^3$, how many different roots does $f\circ g(x)=g\circ f(x)$ have?

I solved it and found $x=-1$ but it says it has two different roots, could someone clarify?

share|cite|improve this question
$g(f(x))-f(g(x))=6x^3(x+1)^2$. So there are two roots : 0 (a triple root) and -1 (a double root) – Ewan Delanoy Jan 23 '12 at 9:33
up vote 4 down vote accepted

Other than the nice answer from Alex, you can also do it concretely: $$f\circ g(x)=f(x^3)=x^6+2x^3=x^3(x^3+2)$$ and $$g\circ f(x)=g(x^2+2x)=(x^2+2x)^3=x^3(x+2)^3.$$ Therefore, $f\circ g(x)=g\circ f(x)$ can be written as $x^3(x^3+2)-x^3(x+2)^3=0$, or equivalently, $$x^3\Big[(x+2)^3-(x^3+2)\Big]=x^3\Big[(x^3+6x^2+12x+8)-(x^3+2)\Big]$$ $$=x^3(6x^2+12x+6)=6x^3(x+1)^2=0,$$ which gives $x=0$ or $x=-1$.

share|cite|improve this answer
Right, I missed $x^3=0$. Thanks. – Gigili Jan 23 '12 at 10:12

$f=g$ when $x=0,2,-1$ as $f=g\implies x(x^2-x-2)=0$.The x we found should also be true for both g and f.Since $f(0)=g(0)=0,f(-1)=g(-1)=-1$ while $g^{-1}(2)=2^{1\over 3}$ while $f(2^{1\over 3})$not equal to 2 which is not possible as an answer.

share|cite|improve this answer
Can you try to make your answer more readable (say by using TeX) and add an explanation? Also, where does "x=2" come from? – Alex Becker Jan 23 '12 at 9:52
Ah, now I see what you did. Thank you for clarifying. – Alex Becker Jan 23 '12 at 10:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.